The Modernity In The Andalusian Muwashshahat - Fares, Issa; Bahloul, Ammar (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research studies the modernity in the Andalusian Muwashshahat, because it was known that The Muwashshahat make the first try to get out from the traditional type of poetry from language side and the rhythm side, So it made a new type of poetry which magnified by a new form that doesn't have less arts than the previous one, although that some critics didn't admit by its poetries . This research will deal with this modernity in the Andalusian Muwashshahat deeply from two sides: first: from language side, because it contained colloquial words not only that, but the Muwashshah was built on a colloquial lock, and it was also contained the frames and its follows, Second: the rhythm side, because it got out from traditional Alphalil Bn Ahmad Alfraheedy's measurings, and it based on tune as a replacement form it in setting the rhyming of the poetry language, And we will deal with all of this by choosing variety poetry syllable, and studying it analyzing study . يدرس هذا البحث الحداثة في الموشحات الأندلسية، فمن المعروف أن الموشحات تشكل أول محاولة ناضجة للخروج على نمط الشعر التقليدي سواء من ناحية اللغة، أو من ناحية الإيقاع، فشكلت نمطاً جديداً من الشعر تميّز بهيئة جديدة لا تقل فنيّة عن سابقتها، وإن لم يعترف بعض النقاد بشعريتها. وسيتناول هذا البحث الحداثة في الموشحات الأندلسية على نحو تفصيلي من ناحيتين: الأولى: ناحية اللغة إذ ضمنتها ألفاظاً عامية، بل وبُني الموشح على خرجة عامية، وشملت أيضاً التراكيب وما يتعلق بها، والثانية: ناحية الإيقاع إذ خرجت على أوزان الخليل بن أحمد الفراهيدي التقليدية، واعتمدت اللحن ليكون بديلاً عنها في ضبط نظم اللغة الشعرية، وسنبحث كل ذلك من خلال اختيار شواهد شعرية متنوعة، ودراستها دراسة تحليلية.